Comparison of back focal plane imaging of nitrogen vacancy centers in nanodiamond and core-shell CdSe/CdS quantum dots - Christinck, J.; Rodiek, B.; López, M.; Georgieva, H.; Hofer, H.; Götzinger, Stephan; Kück, S. (Journal of Physics: Conference Series, 2022)
We report on the characterization of the angular-dependent emission of two different single-photon emitters based on nitrogen-vacancy centers in nanodiamond and on core-shell CdSe/CdS quantum dot nanoparticles. The emitters were characterized in a confocal microscope setup by spectroscopy and Hanbury-Brown and Twiss interferometry. The angular-dependent emission is measured using a back focal plane imaging technique. A theoretical model of the angular emission patterns of the 2D dipoles of the emitters is developed to determine their orientation. Experiment and model agree well with each other.
CRIS-Team Scopus Importer:2022-02-11